OPTIMALISASI KOMUNIKASI KEPERAWATAN MELALUI PENDEKATAN STORYTELLING UNTUK REDUKSI KECEMASAN ANAK PRASEKOLAH SELAMA HOSPITALISASI - Suraya, Citra; Wisuda, Aris Citra; Sansuwito, Tukimin Bin; Dioso, Regidor III (Institut Citra Internasional, 2025)
Hospitalization can be a stressful experience for preschool-aged children, primarily due to limited understanding and anxiety toward the unfamiliar hospital environment. Effective therapeutic communication is essential to help children feel safer and more comfortable during treatment. This community service activity aimed to optimize nursing communication using a storytelling approach as a strategy to reduce anxiety in hospitalized preschoolers. The program was conducted at Siti Fatimah Az-Zahra Regional General Hospital, South Sumatra Province, from March 17 to 21, 2025. It involved 15 bedside nurses in the pediatric ward and 18 hospitalized preschool-aged children. The methods included education and training for nurses on age-appropriate storytelling techniques, followed by direct application with the children. Evaluation was carried out through behavioral observation of children’s anxiety levels before and after the intervention, as well as brief interviews with nurses. The results showed a noticeable reduction in anxiety expressions among most children, such as decreased crying, fearfulness, and resistance to nursing procedures. Nurses also reported improved rapport and interaction with the children through engaging and relevant stories. In conclusion, storytelling proved to be an effective, humanistic, and applicable nursing communication method for reducing hospitalization-related anxiety in preschool children, and it has the potential to be integrated into standard pediatric nursing practices